Oscillations of a flexible beam in cavity flow with tonal sound. Issue 1 (September 2020) - Yokoyama, H; Hibino, K; Nishikawara, M; Yanada, H
Abstract: To establish the methodologies for utilization of oscillation energy in a cavity flow, the self-sustained oscillations in a flow over a cavity with and without a flexible beam are investigated, where stainless steel and aluminium beams are utilized. The coupled simulations for aeroacoustic phenomena and bending vibration of the beam are conducted along with wind tunnel experiments. The measurement of sound pressure level with changing the freestream Mach number shows that intense oscillations occur for the second acoustic mode for both the cavities with a stainless and an aluminium beam along the upstream edge of the cavity while the oscillations with the first mode occur for the cavity without a beam. The computational results show that the beam is vibrated at the natural frequency of each beam, where this frequency can be different from the fundamental frequency of the radiating sound. Also, it is shown that the vibrations become more intense for the cavity flow with the beam along the downstream edge, where the acoustic radiation also becomes more intense.